2021
DOI: 10.3390/nano11112935
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Accumulation of Nano/Microplastics in Plants: A Critical Review

Abstract: The ubiquitous presence of microplastics (MPs) and nanoplastics (NPs) in the environment is an undeniable and serious concern due to their higher persistence and extensive use in agricultural production. This review highlights the sources and fate of MPs and NPs in soil and their uptake, translocation, and physiological effects in the plant system. We provide the current snapshot of the latest reported studies with the majority of literature spanning the last five years. We draw attention to the potential risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(101 citation statements)
references
References 181 publications
(264 reference statements)
2
99
0
Order By: Relevance
“…Depending on endpoints, the smaller size plastic particles (i.e., <5 μm) are generally assumed to be more toxic as compared to larger size materials. 25, 46 A negative response on plant germination was resulted from exposure to MPx/NPx and this response varied with size. With MPx/NPx sizes of <100 nm, 100-400 and >400 nm, germination decreased by 7%, 19% and 27%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on endpoints, the smaller size plastic particles (i.e., <5 μm) are generally assumed to be more toxic as compared to larger size materials. 25, 46 A negative response on plant germination was resulted from exposure to MPx/NPx and this response varied with size. With MPx/NPx sizes of <100 nm, 100-400 and >400 nm, germination decreased by 7%, 19% and 27%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…23, 24 Recently, Azeem et al and Yan et al reported toxicity of MPx/NPx as measured by enzymatic activity and physiological parameters of the plants. 25, 26 However, a mechanistic understanding of the role of material size, concentration and plant species-specific response to MPx/NPx on plants physiological, biochemical, and photosynthetic indices remains elusive. It is clear that investigations of the ecotoxicology of MPx/NPx are needed to gain a comprehensive assessment of their hazard (s) and ultimate risk in agroecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Microplastics in the land mainly interacted with pollutants directly to realize the treatment of pollutants. Of course, the indirect effects of microplastics also affect soil properties [23], such as soil MPs, can provide sorption sites for soil microorganisms, establish unique microbial communities and influence the ecological role of soil microorganisms [24].…”
Section: Activities Of Microplastics In Soilmentioning
confidence: 99%
“…Owing to their capacity to accumulate nanosized particles, organisms may accumulate higher concentrations of NPs in the biological matrix than in other complex matrices [ 32 ]. Following uptake, NPs, especially the small ones (<100 nm), can penetrate the biological membranes [ 46 ] and potentially bioaccumulate in tissues or organs, leading to their transfer along trophic chains. This assumption is supported by experimental evidence [ 47 ].…”
Section: Exposure Assessment: Detection Of Nps In Environmental Samplesmentioning
confidence: 99%